Bioluminescence Resonance Energy Transfer (BRET)‐Based Synthetic Sensor Platform for Drug Discovery. (3rd April 2017) - Woo, Jongchan; Hong, Jason; Dinesh‐Kumar, Savithramma P.
Abstract: Bioluminescence resonance energy transfer (BRET) is a technique that analyzes protein‐protein interactions (PPIs). The unique feature of BRET delineates that the resonance energy is generated by the resonance energy donor, Renilla luciferase by the oxidative decarboxylation of coelenterazine substrate. BRET is superior to FRET where issues such as autofluorescence, photobleaching, and light scattering can occur. Recently, BRET has been applied to design synthetic biosensors for monitoring autophagy in vivo and in vitro. Here, we report the methods for constructing a biosensor of human HsLC3a as a probe for autophagy biogenesis and the optimization of the intramolecular BRET assay that allows for high‐throughput screening of chemical modulators of autophagy. User‐friendly working interface with the BRET‐based synthetic sensor of HsLC3a makes drug discovery easy and amenable for high‐throughput. The BRET protocol described here could be easily applicable to generate other biosensors for monitoring PPIs by measurement of intermolecular BRET. © 2017 by John Wiley & Sons, Inc.